Education for Sustainable Defence and Security - Ivanov, Tilcho (Research Papers, 2022)
The aim of the article is to analyse the challenges facing education in "Economics of Defence and Security", implemented by the Department of National and Regional Security at the University of National and World Economy in Sofia in the transition to sustainable defence and security. The main tasks of the research are to: outline the need for transition to education for sustainable defence and security; present a vision for sustainable defence and security and the adoption of an integrated holistic approach to security; offered a vision of what educational change and practical measures are needed to build sustainable defence and security.
Keywords: Higher education; Sustainable defence and security